Effects of soil properties on arthropod biodiversity in dumpsites in Ibadan, Oyo state, Nigeria (2015)
The impact of soil properties, temperature and relative humidity on arthropod species composition, abundance and diversity was investigated in Apete and Aba-eku dumpsites and in a control site in Ibadan, Oyo state, Nigeria. Ten 250g size pitfalls one third filled with 5% formalin were placed in each point in order to trap and preserve the arthropods. The arthropods trapped in each pitfall were preserved in separate specimen bottle containing 70% ethanol before identification. A total of 20 soil samples were collected from the sites using Auger and analyzed for particle size distribution, bulk density, moisture content, water holding capacity, porosity, organic matter, pH, total nitrogen, available phosphorus, potassium, calcium in (mol/kg-1) and available iron and zinc in mg/kg-1. Analysis of variance (ANOVA) and Duncan’s multiple range test (DMRT) were conducted to compare the mean values of the soil properties and arthropods abundance. A total of 4,763 arthropods were recorded belonging to 17 orders. Twenty six families of arthropods containing 31 species were recorded in Aba-Eku, while 24 families with 24 species were encountered in Apete and 19 families with 21 species were recorded for the control site. Soil parameters examined showed significant difference (p>0.05) across the three sites. The high percentage abundance of Dipterans (Musca domestica) and heavy metal recorded, Zinc and Iron indicates that the environments were polluted. Pearson correlation coefficient (r) showed negative correlation for the relative humidity and temperature to the arthropods abundance. The distinct taxa found in Apete and Aba-eku suggest that the organic input from residential areas around the dump sites favoured their abundance.